Are clinical delusions adaptive? - Lancellotta, Eugenia (Wiley Interdiscip Rev Cogn Sci, 2019)
Delusions are symptoms of psychiatric disorders such as schizophrenia and dementia. By and large, delusions are characterized by their behavioral manifestations and defined as irrational beliefs that compromise good functioning. In this overview paper, we ask whether delusions can be adaptive notwithstanding their negative features. Can they be a response to a crisis rather than the source of the crisis? Can they be the beginning of a solution rather than the problem? Some of the psychological, psychiatric, and philosophical literature has recently suggested that they can. We consider different types of delusions and different ways in which they can be considered as adaptive: psychologically (e.g., by increasing wellbeing, purpose in life, intrapsychic coherence, or good functioning) and biologically (e.g., by enhancing genetic fitness). Although further research is needed to map the costs and benefits of adopting and maintaining delusional beliefs, a more nuanced picture of the role of delusions in people's lives has started to emerge. Philosophy > Representation. Philosophy > Knowledge and Belief. Neuroscience > Cognition.